THE INFLUENCE OF HALAL LABELS, HALAL AWARENESS AND PRICE ON INTEREST IN ONLINE SHOPPING FOR FOOD PRODUCTS: THE ROLE OF DEMOGRAPHIC CHARACTERISTICS AS MODERATING - Hafidhah; Khairul Amri; Farrel Yustia Trianda (Journal of Management and Islamic Finance, 2024)
Muslim customers worldwide pay close attention to the halal label as proof that the product conforms to their religious values. Halal awareness refers to how well Muslims understand matters related to ​​halal. One very important factor that can influence shopping interest is product price. Halal labels, awareness, and Prices are important factors in increasing interest in online shopping for food products. This is based on research that tries to test and analyze the influence of halal labels, halal awareness, and prices on online shopping interest in food products, which is moderated by demographic characteristics (gender and age). The method used was the Structural Equation Modelling - AMOS with 152 FEBI UIN Ar-Raniry student respondents. The results show that halal labels and halal awareness do not significantly influence online shopping interest, while Price has a positive and significant influence. Demographic characteristics moderated this effect by 47.4%. These findings highlight that consumer behavior in online shopping is highly complex, influenced by a combination of psychological factors (halal awareness), rational factors (price), and demographic characteristics. While halal labels and awareness hold significant importance in certain contexts, they tend to be less relevant compared to economic factors such as price in the realm of online shopping, particularly when demographic characteristics serve as moderating factors.